1999
DOI: 10.1086/514314
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Ebola (Subtype Reston) Virus in the Philippines, 1996

Abstract: Ebola (subtype Reston [EBO-R]) virus infection was detected in macaques imported into the United States from the Philippines in March 1996. Studies were initiated in the Philippines to identify the source of the virus among monkey-breeding and export facilities, to establish surveillance and testing, and to assess the risk and significance of EBO-R infections in humans who work in these facilities. Over a 5-month period, acutely infected animals were found at only one facility, as determined using Ebola antige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
112
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(114 citation statements)
references
References 9 publications
0
112
0
2
Order By: Relevance
“…Tissues and sera from cynomolgus monkeys (Macaca fascicularis) naturally infected with Ebola virus subtype Reston in the Philippines were used as clinical specimens. These specimens had been kept either at Ϫ80°C or in liquid nitrogen since an outbreak in 1996 (12). The status of infection with subtype Reston in these animals was established previously (12).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissues and sera from cynomolgus monkeys (Macaca fascicularis) naturally infected with Ebola virus subtype Reston in the Philippines were used as clinical specimens. These specimens had been kept either at Ϫ80°C or in liquid nitrogen since an outbreak in 1996 (12). The status of infection with subtype Reston in these animals was established previously (12).…”
Section: Methodsmentioning
confidence: 99%
“…These specimens had been kept either at Ϫ80°C or in liquid nitrogen since an outbreak in 1996 (12). The status of infection with subtype Reston in these animals was established previously (12). Liver and spleen tissues (approximately 10% [wt/vol]) were homogenized in 0.05% Tween 20, 1% Triton X-100, and 5% nonfat milk in phosphate-buffered saline (PBS).…”
Section: Methodsmentioning
confidence: 99%
“…Aerosol is not thought to be the ordinary route of transmission in natural outbreaks; however, there have been reports of naive NHP infected across the room from experimentally infected NHP and human cases in which direct contact with infected patients could not be demonstrated, suggesting aerosol transmission [60,67,68]. Experimental studies have shown that filoviruses are relatively stable in aerosol, can survive on surfaces for prolonged periods of time, and are able to infect susceptible naive animals and cause lethal disease when inhaled [40][41][42][43][44]61,69,70].…”
Section: Animal Models Of the Human Diseasementioning
confidence: 99%
“…However, Reston ebolavirus (RESTV) is uniquely Asian in origin. RESTV has been identified in bats and primates (Miranda et al, 1999;Rollin et al, 1999;Taniguchi et al, 2011), as well as swine (Barrette et al, 2009;Sayama et al, 2012). However, in humans RESTV appears to be nonpathogenic and transmits poorly for reasons that are not fully understood (Miranda et al, 1999).…”
Section: Introductionmentioning
confidence: 99%